Relation Of Resilience With Psychological Distress On Tobacco Farmers In Kalisat District, Jember Regency - Wuryaningsih, Emi Wuri; Holivia, Tria Mega; Hadi K, Enggal (Jurnal Keperawatan, 2019)
Tobacco farmers are prone to various health problems both physically and psychologically or mentally due to several problems such as Green Tobacco Sickness (GTS), crop failure and weather anomalies. Resilience is one of the coping mechanisms that can be used to prevent psychological distress. This study used a cross-sectional study design with cluster random sampling technique, a sample of 96 respondents. The study was conducted in February-March in Kalisat District, Jember Regency. Bivariate analysis used Pearson correlation (Î±